Perancangan Aplikasi Berbasis Android Untuk Merk Baju Pantai Pasir Dengan Disk Skema Menggunakan Algoritma Hungaria - Mukhlis Hafidh Khoiriswanto; Muhammad Daffatama Nopriliano; Daniel Agustino; Kiki Yulianto; Aries Saifudin (Journal of Research and Publication Innovation, 2023)
Currently, the world of technology is experiencing rapid progress and development. One of the rapid advancements is Android. A part from technology, rapid development is also seen in the fashion industry. The most common problem in this area is marketing. Time is running too fast also causes fierce competition for creativity. In selling, the media is involved in important issues that can attract buyers and increase sales. Mobile is the process of developing applications for mobile devices such as cell phones or PDAs. If the mobile app production already exists or can be downloaded by the user depending on the software platform. Sand seaside clothing logo application based on Android with a discount system using the Hungarian algorithm. Hungary's algorithm is an easy way to determine which discount is most profitable for shoppers to attract buyers' interest in this app's clothing brands. This android-based application provides information about products that are packaged neatly and beautifully so that buyers can see clearly the description, model and price of the product to be purchased. The Sand beach logo apparel Android application also has an administrator account that can systematically and systematically access and manage buyer orders.